From anti-theatricality to the contemporary stage: visions of the other in theatricality (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
From Plato to the present day, the theatricality has been questioned through trans-historical theoretical prisms, arbitrarily contested for philosophers, artists and art critics. From the perspective of the actor-director-spectator triad, the aim is to understand the nuances between that one and anti-theatricality, whose intentions are not expected to be separate, but rather a feedback that takes place between the contradictions of their similarities and differences in the theatre. The other – individual, current, time, vision, artifice - becomes a key element in bringing the production closer to the perception of theatricality on the contemporary stage, through its particularities in the collective between art and life.
Keywords: theatricality; anti-theatricality; other; vision; current